Sammlung "Junge Kunst". - Rickmann, Herbert; Salzmann, Siegfried; Schmidt, Ulrich (Duisburg : König-Brauerei, 1978)
Agam, Yaacov ; Antes, Horst ; Bak, Imre ; Bernhard, Franz ; Beuys, Joseph ; Böhm, Hartmut ; Brüning, Peter ; Brus, Johannes ; Cadora, Georg ; Dine, Jim ; Dohr, Günther ; Dreher, Peter ; Estes, Richard ; Fajo, Janos ; Fink, Anton ; etc.
boek